Polyketides with quorum sensing inhibitory activity from the marine-derived fungus Aspergillus sp. ZF-79. Issue 11 (1st November 2020) - Zhang, Fei; Kong, Fan-Dong; Ma, Qing-Yun; Xie, Qing-Yi; Zhou, Li-Man; Zhao, You-Xing; Guo, Lei
Abstract: Seven compounds were isolated from a marine-derived fungus Aspergillus sp. ZF-79, including three new polyketides (1 –3 ), named asperochrins D-F, along with four known compounds 4–7 . Their structures were determined on the basis of spectroscopic methods. All the compounds were tested for quorum sensing inhibitory (QSI) activity. Compounds 1, 3, 4, 5, and 6 exhibited QSI activity against Chromobacterium violaceum CV026 with MIC values of 50, 100, 50, 50, and 6.25 μM, respectively. Abstract :